Biossecagem: uma alternativa para os resíduos sólidos urbanos - Feltrim, Fernanda (2020)
The generation of municipal solid waste (MSW) is constantly growing, a consequence of a series of factors, such as population growth and society’s consumption habits. As a result of high generation and more restrictive legislation, waste management has become a major challenge for managers. Currently, in Brazil, there are few widespread techniques for the reuse of MSW, including composting and recycling. Recently, other techniques are being developed, mainly those aimed at the energy use of waste. Among the techniques, there is biodrying, which aims to dry the residues through aerobic degradation of easily degradable organic matter together with excessive and controlled aeration. Taking into account the above, a rotary drum was designed, built and tested to perform biodrying tests with synthetic municipal solid waste. The experimental planning was carried out through a factorial design, with the following factors being used: organic matter content, aeration rate and interval between rotations, with two levels. Analyzes of moisture content, volatile and fixed solids, calorific value and granulometry were performed for the input and output waste of the biodrying process. During the first test campaign it was noted that when there was moisture loss, it didn’t exceed 3%, probably due to the short time in which the temperature remained high and, also, due to the lack of formation of air flow inside the reactor. There was a reduction in the content of volatile solids in the tests carried out with residues that used 60% of organic matter, while for the tests that used 40% of organic matter this trend wasn’t observed. Mesophilic temperatures were observed, decreasing according to the rotation of the reactors. The tests carried out with a higher amount of recyclables resulted in values of net calorific value higher than those carried out with a lower amount of recyclables. After changes in the reactors, an increase in gravimetry and an increase in the particle size, no mesophilic temperatures were observed inside the reactor, but a behavior similar to that of the external temperature. However, the moisture content reached 2.6%, probably due to the convective action of aeration. As a consequence of the reduction in moisture contente in all batches of biodrying in the second test campaign, there was an increase in the calorific value, reaching 101%. The batch carried out with 60% of organic matter in the second campaign, aeration rate of 1 L kg-1 min-1 and interval between rotations of 3 hours resulted in a greater difference between the values of entry and exit, that is, it removed more moisture and had the greatest increase in calorific value. Rotary drum can be used for biodrying, and this technique is promising in view of the world and national scenario in the scope of municipal solid waste.